Trait choice profoundly affected the ecological conclusions drawn from functional diversity measures - Linhai Zhu (Nature Portfolio, 2017)
Abstract Although trait choice is crucial to quantify functional diversity appropriately, the quantitative methods for it are rarely compared and discussed. Meanwhile, very little is known about how trait choice affects ecological conclusions drawn from functional diversity measures. We presented the four methods of trait selection as alternatives to the ordination axis-based method, which directly identify a subset of key traits to represent the main variation of all the traits. To evaluate their performance, we compared the closeness of association obtained by different methods between species richness and functional diversity indices (FAD, FD, Q, FDis) in the six ecosystems. The evaluation was also benchmarked against the results obtained by calculating the possible indices using all the trait combinations (the complete search method). We found that the trait selection methods were potential alternatives to axis-based method to gain a mechanistic understanding of functional responses and effects of traits, while these methods as well as the axis-based method possibly use mismatched information to interpret the investigated ecosystem properties. Trait choice profoundly affected the ecological conclusions drawn from functional diversity measures. The complete search method should be used to assess the rationale of different trait choice methods and the quality of the calculated indices.